Mass customization: fundamental modes of operation and study of an order fulfilment model - Brabazon, Philip G. (2006)
This research studies Mass Customization as an operations strategy and model. Opinions differ over whether MC should be a label for a specific business model in which customers select from pre-engineered product options, or whether it should be interpreted as a performance goal that has wider relevance. In this research it is viewed as the latter and a manufacturing enterprise is considered to be a mass customizer if it gives its customers the opportunity to have a product any time they want it, anywhere they want it, any way they want it and in any volume they want it, and at the same time brings the benefits that are associated with mass operations, in particular those of price and quality.